1989
DOI: 10.1007/bf01972832
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leukotriene-B4 receptor antagonist, SC-41930, on acetic acid-induced colonic inflammation

Abstract: SC-41930, 7-[3-(4-acetyl-3-methoxy-2-propylphenoxy)-propoxy]-3,4-dihydro-8-p ropyl- 2H-1-benzopyran-2-carboxylic acid, is a potent in vitro leukotriene-B4 (LTB4) receptor antagonist. LTB4 levels are elevated in colonic tissue of inflammatory bowel disease (IBD) patients which may account for the high degree of neutrophil (PMN) infiltration. The guinea pig acetic acid-induced colonic inflammation model has characteristics of IBD including PMN infiltration, edema, ulceration and necrosis. The model was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…The results obtained revealed that all the doses of morin which reduced macroscopic colonic damage significantly inhibited LTB 4 synthesis, and this inhibition was maximal at the highest dose of morin assayed (200 mg/kg). Since LTB 4 has been shown to potently promote neutrophil chemotaxis, adherence and degranulation in the TNBS-treated colon [27], this mechanim may account for the aforementioned decrease in MPO colonic activity. Furthermore, the diminished number of neutrophils in the colonic tissue in the morin-treated groups (10 and 25 mg/kg) may, at least partially, contribute to the reduction in LTB 4 production by the colonic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained revealed that all the doses of morin which reduced macroscopic colonic damage significantly inhibited LTB 4 synthesis, and this inhibition was maximal at the highest dose of morin assayed (200 mg/kg). Since LTB 4 has been shown to potently promote neutrophil chemotaxis, adherence and degranulation in the TNBS-treated colon [27], this mechanim may account for the aforementioned decrease in MPO colonic activity. Furthermore, the diminished number of neutrophils in the colonic tissue in the morin-treated groups (10 and 25 mg/kg) may, at least partially, contribute to the reduction in LTB 4 production by the colonic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Ocete/Gá lvez/Crespo/Cruz/Gonzá lez/ Torres/Zarzuelo LTB 4 is considered as an important proinflammatory mediator in colonic inflammation [23,25], and inhibition of LTB 4 synthesis [25,26] or blockade of the LTB 4 receptor [27] is beneficial in experimental colitis, whereas administration of exogenous LTB 4 exacerbates inflammation [28]. Because morin is an inhibitor of 5-lipoxygenase [29], we tested whether its intestinal anti-inflammatory activity could be ascribed to a reduction in colonic LTB 4 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the exact role of these ligands and the two BLTR subtypes in IBD remains to be established. Whereas different BLTR antagonists inhibit colonic inflammation and neutrophil infiltration in animal models of IBD (Fretland et al, 1990(Fretland et al, , 1991, BLT 2 R-deficient mice exhibit exacerbated colonic inflammation (Iizuka et al, 2010).…”
Section: F Potential Therapeutic Applicationsmentioning
confidence: 99%
“…57 Fretland et al 57 investigated in several animal species (rat, guinea pig, and rabbit) the influence of locally administration of the BLT 1 antagonist SC-411930 on acetic acid-induced colitis. 58 They found that LTB 4 receptor antagonist substantially ameliorates colonic inflammation. However, it is not likely that protection in these models was due to blockade of the LTB 4 /BLT 1 pathway mediating chemotaxis of neutrophils and possibly monocytes, rather than T cells.…”
Section: Mhc Class I-restricted Cd8mentioning
confidence: 99%